Sustaining and supporting the momentum of enduring pandemic practices - Cathy Box; Mary-Catherine Dean; Sarah McCorkle; William O'Brochta (To Improve the Academy, 2024)
Faculty members impacted by the COVID-19 pandemic inadvertently participated in a historic, widespread, and rapidly occurring educational development phenomenon: the global shift toward emergency remote teaching. We surveyed faculty members (n = 502) at four different institutions (a community college and a small, medium-sized, and large university) and collected self-reported data on faculty members’ continued use of educational technology tools or teaching techniques that they adopted for the first time during the pandemic. Faculty respondents also shared their perceptions on why this change to their teaching was valuable. Approximately 62% of the faculty surveyed reported their continued use of an educational technology tool, and 34% reported their continued use of a teaching technique or strategy. Higher education institutions must now consider the implications of these enduring pandemic practices, evaluate their effectiveness, and work to sustain the skill-building momentum of faculty who have invested time in adopting new technology tools and teaching techniques.